An Ethical Assessment Tool (ETHAS) to Evaluate the Application of Assisted Reproductive Technologies in Mammals' Conservation: The Case of the Northern White Rhinoceros (Ceratotherium simum cottoni) - de Mori, Barbara; Spiriti, Maria Michela; Pollastri, Ilaria; Normando, Simona; Biasetti, Pierfrancesco; Florio, Daniela; Andreucci, Francesco; Colleoni, Silvia; Galli, Cesare; Göritz, Frank; Hermes, Robert; Holtze, Susanne; et al. (Animals, 2021)
Assisted reproductive technologies (ARTs) can make a difference in biodiversity conservation. Their application, however, can create risks and raise ethical issues that need addressing. Unfortunately, there is a lack of attention to the topic in the scientific literature and, to our knowledge, there is no tool for the ethical assessment of ARTs in the context of conservation that has been described. This paper reports the first applications of the Ethical Assessment Tool (ETHAS) to trans-rectal ovum pick-up (OPU) and in vitro fertilization (IVF) procedures used in a northern white rhinoceros (Ceratotherium simum cottoni) conservation project. The ETHAS consists of two checklists, the Ethical Evaluation Sheet and the Ethical Risk Assessment, and is specifically customized for each ART procedure. It provides an integrated, multilevel and standardized self-assessment of the procedure under scrutiny, generating an ethical acceptability ranking (totally, partially, not acceptable) and a risk rank (low, medium, high), and, hence, allows for implementing measures to address or manage issues beforehand. The application of the ETHAS to the procedures performed on the northern white rhinoceros was effective in ensuring a high standard of procedures, contributing to the acceptability and improved communication among the project's partners. In turn, the tool itself was also refined through an iterative consultation process between experts and stakeholders.
Keywords: ethical review process; northern white rhinoceros; animal welfare; ethical self-assessment; conservation ethics; assisted reproductive technologies; ethical risk assessment